Extended Narrow-Line Region in Seyfert Galaxies - Congiu, Enrico; Contini, Marcella; Ciroi, Stefano; Cracco, Valentina; Di Mille, Francesco; Berton, Marco; Frezzato, Michele; La Mura, Giovanni; Rafanelli, Piero (Frontiers in Astronomy and Space Sciences, 2017)
We present our recent results about the extended narrow-line region (ENLR) of two nearby Seyfert 2 galaxies (IC 5063 and NGC 7212) obtained by modelling the observed line profiles and spectra with composite models (photoionization+shocks) in the different regions surrounding the AGN. Then, we compare the Seyfert 2 ENLRs with the very extended one recently discovered in the narrow-line Seyfert 1 (NLS1) galaxy Mrk 783. We have found several evidences of interaction between the ISM of the galaxies and their radio jets, such as a) the contribution of shocks in ionizing the high velocity gas, b) the complex kinematics showed by the profile of the emission lines, c) the high fragmentation of matter, etc. The results suggest that the ENLR of IC 5063 have a hollow bi-conical shape, with one edge aligned to the galaxy disk, which may cause some kind of dependence on velocity of the ionization parameter. Regarding the Mrk 783 properties, it is found that the extension of the optical emission is almost twice the size of the radio one and it seems due to the AGN activity, although there is contamination by star formation around 12 arcsec from the nucleus. Diagnostic diagrams excluded the contribution of star formation in IC 5063 and NGC 7212, while the shock contribution was used to explain the spectra emitted by their high velocity gas.